Trends and Hotspots in International Research on Problem Solving in Physics Education - Mardianti, Fani; Liliawati, Winny; Sinaga, Parlindungan; Wandi, Wandi; Karimi, Amir (STKIP Singkawang, 2024)
Problem solving in physics education that have not been resolved to date causes obstruction of various interests. To comprehensively analysis the global application trends of problem solving in physics education and identify research points that promise problem solving in physics material based on bibliometrics and visual analysis. Publications related to problem solving in physics education from 2003 to 2023 were retrieved from the Scopus. The nation, institution, publication year, author, journal, average citations per item, H index, title, publication keywords evaluated. The VOS-viewer software was used to evaluate term co-occurrence results in order to anticipate problem-solving hotspots in physics education. There were 421 articles in all. (1) In general, the quantity of problem solving in physics education papers has increased during the last 20 years. The top three countries (USA, Indonesia, and Australia) accounted for 63.22% of all published articles. The United States has the most citation. The largest contributor is Universitas Pendidikan Indonesia. Suhandi, A. is the professor with the most articles published in the topic of problem solving in physics education. (2) The research field is organized into seven clusters: